Fetoplacental endothelial dysfunction in maternal hypercholesterolemia and obesity in pregnancy - Pardo, Fabián (2014)
Human fetoplacental vascular function is altered in several pathologies of pregnancy as a result of endothelial dysfunction. Pregnancy is a physiological condition coursing with increased circulating plasma levels of cholesterol in the mother, to respond to the higher demands from the growing fetus. An abnormal increase in maternal plasma cholesterol configures a pathological state referred as maternal supraphysiological hypercholesterolemia (MSPH). In MSPH, L-arginine transport and synthesis of nitric oxide (i.e., L-arginine/NO signalling pathway) as well as arginases/urea cycle in the fetoplacental endothelium are altered. Equally, an increase in the physiological gain of weight in pregnant women could end with obese women at the end of pregnancy leading to a condition referred as obesity in pregnancy (OP). OP seems to be also associated with alterations in the L-arginine/NO signalling pathway in endothelium in animal models; however, nothing is known regarding alterations of the human fetoplacental endothelium in OP. Insulin, adenosine and NO are vasodilators in the fetoplacental vascular bed, and a role for these molecules is proposed in MSPH and OP. Alternatively, involvement of intracellular pH modulation and the potential involvement of adenosine receptors is proposed as phenomena that could improve endothelial dysfunction associated with these diseases of pregnancy.